The learning preferences and motivation among real estate undergraduates - Cheng, Siew Lee, 1995-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Sains (Pengurusan Harta Tanah)) - Universiti Teknologi Malaysia, 2019